The Toxicity of Iodinated Radiographic Contrast Agents in the Clinical Practice - Andreucci, Michele; Faga, Teresa; De Sarro, Giovanbattista; Michael, Ashour (Journal of Nephrology Advances, 2015)
Iodinated radiographic contrast agents (IRCA) are pharmaceutical agents used to improve the visibility of internal organs and structures in X-ray based imaging techniques. However, IRCA may have adverse unwanted effects, ranging from a mild inconvenience, such as itching, to a life-threatening emergency. The adverse effects of IRCA include delayed allergic reactions, anaphylactic reactions, and/or cutaneous reactions. But exposure to IRCA may be associated also with the development of either hyperthyroidism or hypothyroidism, presumably due to the effect of free, biologically active elemental iodine ions present in these agents. Among the side effects associated with the use of intravascular injection of IRCA, Contrast-induced nephropathy (CIN) is undoubtedly their most important and frequent well known adverse reaction. The pathogenesis of CIN is discussed in detail including the factors that increase the incidence of CIN, the main ones being pre-existing renal impairment, particularly when associated with diabetes mellitus. Finally, the measures to reduce the nephrotoxicity of IRCA are suggested beginning with monitoring renal function, discontinuation of potentially nephrotoxic drugs, use of either iodixanol or iopamidol at the lowest dosage possible. The main procedure for prevention of CIN is an adequate hydration of the patient with either isotonic sodium chloride or sodium bicarbonate solutions. A long list of references is provided that will enable readers a deep appreciation of the topic.
Keywords: Contrast-Induced Nephropathy; Contrast-Induced Acute Kidney Injury; Acute Renal Failure; Radiographic Contrast Media; Iodinated Contrast Material; Toxicity of Contrast Media; Renal Injury.